2017
DOI: 10.1002/joc.5114
|View full text |Cite
|
Sign up to set email alerts
|

The influence of station density on climate data homogenization

Abstract: ABSTRACT:Relative homogenization methods assume that measurements of nearby stations experience similar climate signals and rely therefore on dense station networks with high-temporal correlations. In developing countries such as Peru, however, networks often suffer from low-station density. The aim of this study is to quantify the influence of network density on homogenization. To this end, the homogenization method HOMER was applied to an artificially thinned Swiss network.Four homogenization experiments, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 45 publications
1
74
1
5
Order By: Relevance
“…On a daily timescale, this reduction is 0.10 (TX) and 0.13 (TN) for station pairs within 300 km of distance and 0.06 (PRCP) for stations within 100 km of distance. These findings confirm the assumption by Gubler et al (2017) that the strong differences in correlation coefficients between station networks of the Peruvian Andes and Switzerland may not be explained by unequal climate regimes alone. Hypothesizing that UDQIs occur more frequently in the station networks of developing than developed countries, a higher frequency of such errors can be expected in tropical areas than in mid-latitudes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…On a daily timescale, this reduction is 0.10 (TX) and 0.13 (TN) for station pairs within 300 km of distance and 0.06 (PRCP) for stations within 100 km of distance. These findings confirm the assumption by Gubler et al (2017) that the strong differences in correlation coefficients between station networks of the Peruvian Andes and Switzerland may not be explained by unequal climate regimes alone. Hypothesizing that UDQIs occur more frequently in the station networks of developing than developed countries, a higher frequency of such errors can be expected in tropical areas than in mid-latitudes.…”
Section: Discussionsupporting
confidence: 89%
“…Reducing the spatial density of available data normally decreases the quality of the results such as for data homogenization (Caussinus and Mestre, 2004;Domonkos, 2013;Gubler et al, 2017). With the present study, however, we have demonstrated that removing time series segments affected by UDQIs increases the overall quality of the dataset, and the results of climatological analyses are consequently more coherent and reliable.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Gubler et al . () performed four experiments on Peruvian and Swiss networks in order to assess the influence of station density on climate data homogenization.…”
Section: Introductionmentioning
confidence: 99%